2020
DOI: 10.1186/s12910-020-00555-6
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ attitudes in relation to end-of-life decisions in Neonatal Intensive Care Units: a national multicenter survey

Abstract: Background End-of-life decisions for neonates with adverse prognosis are controversial and raise ethical and legal issues. In Greece, data on physicians’ profiles, motivation, values and attitudes underlying such decisions and the correlation with their background are scarce. The aim was to investigate neonatologists' attitudes in Neonatal Intensive Care Units and correlate them with self-reported practices of end-of-life decisions and with their background data. Methods A structured questionnaire was distrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The importance of religion as a parameter influencing ethical decision making in neonatal care has also been highlighted in the EURONIC project [ 41 ]. Similarly, other research has shown religious beliefs to be among the most common factors influencing cardiopulmonary resuscitation and neonatal intensive care decisions in extremely preterm neonates [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 92%
“…The importance of religion as a parameter influencing ethical decision making in neonatal care has also been highlighted in the EURONIC project [ 41 ]. Similarly, other research has shown religious beliefs to be among the most common factors influencing cardiopulmonary resuscitation and neonatal intensive care decisions in extremely preterm neonates [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 92%
“…Differences in attitudes towards decision making at the end of life have also been noted between linguistic regions of Switzerland, with German-speaking parents preferring for the family to have the final call, while French- and Italian-speakers prefer physicians to have more decision making power ( 69 ). Religion, culture, racial bias and acceptance of diagnosis have also been cited in the literature as reasons for variation in decision making by neonatal teams ( 54 , 70 , 71 ). Personal biases might also play a role—clinicians who have children are more likely to be conservative in managing periviable infants ( 72 ).…”
Section: Literature Reviewmentioning
confidence: 99%